2009
DOI: 10.1103/physrevstab.12.041301
|View full text |Cite
|
Sign up to set email alerts
|

Cyclotron spatial autoresonance acceleration model

Abstract: An autoresonance electron acceleration phenomenon in the combined steady-state inhomogeneous magnetic and microwave fields is analytically studied. Equations describing the evolution of the phase shift between the particle velocity and the microwave electric field, total energy, and longitudinal velocity of the electron are obtained. Linear and parabolic profiles of the magnetic field are examined. It is shown that the proper choice of the magnetic heterogeneity degree, the microwave electric field value, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…One may enhance the cyclotron resonance acceleration by applying a time-varying magnetic field 24,25 or a stationary inhomogeneous magnetic field. [26][27][28][29] In Ref. 26, the electron cyclotron resonance acceleration by an intense plane-wave laser pulse has been investigated.…”
Section: Introductionmentioning
confidence: 99%
“…One may enhance the cyclotron resonance acceleration by applying a time-varying magnetic field 24,25 or a stationary inhomogeneous magnetic field. [26][27][28][29] In Ref. 26, the electron cyclotron resonance acceleration by an intense plane-wave laser pulse has been investigated.…”
Section: Introductionmentioning
confidence: 99%
“…Although the ring of high-energy electrons was observed in the first experiments on the ECR heating of mirror trap plasmas [12][13][14] and a collective philosophy to explain the discharge ring structure was developed [15], only recently it has been demonstrated how the ring is self-organized and that the ring is comprised of hot and superhot electrons [16]. An acceleration of electrons to super-high energies is attributed to the space cyclotron autoresonance phenomenon [17,18]. Elsewhere [4] it is shown that a direct contact of the ring with the plasma electrode that provokes the bombardment of the plasma electrode by energetic ring particles results in the forming of a near-electrode-surface layer of the secondary low-energy electrons.…”
Section: Introductionmentioning
confidence: 99%
“…The hot electrons very likely gain their energies due to collective plasmawave interactions in the cyclotron and high-hybrid resonance conditions [6]. A mechanism of electron heating to energies of hundreds kilo-electron-volts is attributed to the space cyclotron autoresonance electron-microwaves interaction [7,8]. Recently this autoresonance interaction has helped to understand how electron rings, which are experimentally observed in the magnetic mirror traps [9][10][11], are self-organized [12].…”
Section: Introductionmentioning
confidence: 99%